The Influence of Employability Skills on Teaching and Self-Efficacy on the Interest in Becoming Teachers - Kurniawati, Hanik; Puspasari, Durinta (Universitas Negeri Semarang, 2024)
This research aims to determine the influence of employability skills on teaching and self-efficacy on interest in becoming teachers among students in the Office Administration Education Study Program. This research examines the issue of employability skills on teaching or teaching skills and self-confidence or self-efficacy which is associated with interest in becoming a teacher. This research uses an explanatory method with a quantitative approach. The sample in this study was all students of the Office Administration Education Study Program Class of 2020. The sample for this study used a saturated sampling technique. The data collection technique used in this research used questionnaires and documentation. The data analysis method used is multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 22 software. The results of the t test in this study show that employability skills on teaching have no effect on interest in becoming a teacher, self-efficacy has an effect positive and significant on interest in becoming a teacher, and the results of the f test show that simultaneously employability skills on teaching and self-efficacy have a positive and significant effect on interest in becoming a teacher among students in the Office Administration Education Study Program.